2012
DOI: 10.1186/1550-2783-9-51
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation and doping-related factors in high-level sailing

Abstract: BackgroundAlthough dietary supplements (DSs) in sports are considered a natural need resulting from athletes’ increased physical demands, and although they are often consumed by athletes, data on DS usage in Olympic sailing are scarce. The aim of this study was to study the use of and attitudes towards DSs and doping problems in high-level competitive sailing.MethodsThe sample consisted of 44 high-level sailing athletes (5 of whom were female; total mean age 24.13 ± 6.67 years) and 34 coaches (1 of whom was fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 49 publications
(50 reference statements)
6
36
0
9
Order By: Relevance
“…In the present study, the most frequent reason mentioned by the athletes who are not supplement users was that there was no need for supplementation. These findings corroborate those of other studies, Rodek et al [18] and Nieper [25]. Lack of knowledge was another reason for not consuming supplements, which is in agreement with previous studies that found that the greater the knowledge of supplementation the more willing the athlete is to use supplements [2].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In the present study, the most frequent reason mentioned by the athletes who are not supplement users was that there was no need for supplementation. These findings corroborate those of other studies, Rodek et al [18] and Nieper [25]. Lack of knowledge was another reason for not consuming supplements, which is in agreement with previous studies that found that the greater the knowledge of supplementation the more willing the athlete is to use supplements [2].…”
Section: Discussionsupporting
confidence: 83%
“…However, in most studies cited here, dietitians are not among the main three information sources [5][6][7]18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optimal nutrition may reduce fatigue and injuries, promote recovery from injuries, optimize the body's energy stores and consequently positively influence one's health status [18][19][20]. Due to the training duties and performances, dancers are frequently unable to eat adequately and therefore the relatively high prevalence of the NS in our participants (almost 2/3 of the dancers consume the NS) is not surprising and is consistent with previous reports [3,5].…”
Section: Discussionsupporting
confidence: 78%
“…Many controversies remain about the possible efficacy and necessity of this behavior [18]. Yet it is also confirmed that the NS provide potentially important nutrients for those individuals who are involved in physically demanding activities [19]. Nutritional supplementation cannot replace a dancer's genetic potential, training regime or overall psychosocial preparation, but the most favorable NS strategies have been studied and have often proven to be beneficial.…”
Section: Discussionmentioning
confidence: 99%